2017
DOI: 10.1002/rnj.280
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Original and Short Versions of the Dynamic Gait Index in Predicting Falls in Stroke Survivors

Abstract: DGI-8 and DGI-4 can be useful for predicting falls of stroke patients, allowing better quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…To assess fall risk, performance-oriented balance tests are commonly used. All the tests below were described to be able to identify individuals who are prone to falls or to predict the probability of falls in various populations ( Shumway-Cook et al, 2000 ; Hall et al, 2004 ; An et al, 2017 ; Cleary and Skornyakov, 2017 ; Raîche et al, 2000 ; Jeon and Kim, 2017 ; Lauretani et al, 2019 ; Rose et al, 2002 ). Nine studies ( Grigorova-Petrova et al, 2015 ; Yesilyaprak et al, 2016 ; Sun et al, 2018 ; Wu et al, 2019 ; Cicek et al, 2020 ; Fakhro et al, 2020 ; Babadi and Daneshmandi, 2021 ; Ramnath et al, 2021 ; Zahedian-Nasab et al, 2021 ) assessed fall risk using the Timed Up and Go Test (TUG, Mathias et al, 1986 ), two ( Monteiro-Junior et al, 2017 ; Rica et al, 2020 ) a slightly modified version of the TUG, the 8-Foot Up and Go test (8UG, Rikli and Jones, 1999 ), and one ( Delbroek et al, 2017 ) the instrumented TUG (iTUG, Salarian et al, 2010 ), which uses portable inertial sensors for a more detailed analysis.…”
Section: Resultsmentioning
confidence: 99%
“…To assess fall risk, performance-oriented balance tests are commonly used. All the tests below were described to be able to identify individuals who are prone to falls or to predict the probability of falls in various populations ( Shumway-Cook et al, 2000 ; Hall et al, 2004 ; An et al, 2017 ; Cleary and Skornyakov, 2017 ; Raîche et al, 2000 ; Jeon and Kim, 2017 ; Lauretani et al, 2019 ; Rose et al, 2002 ). Nine studies ( Grigorova-Petrova et al, 2015 ; Yesilyaprak et al, 2016 ; Sun et al, 2018 ; Wu et al, 2019 ; Cicek et al, 2020 ; Fakhro et al, 2020 ; Babadi and Daneshmandi, 2021 ; Ramnath et al, 2021 ; Zahedian-Nasab et al, 2021 ) assessed fall risk using the Timed Up and Go Test (TUG, Mathias et al, 1986 ), two ( Monteiro-Junior et al, 2017 ; Rica et al, 2020 ) a slightly modified version of the TUG, the 8-Foot Up and Go test (8UG, Rikli and Jones, 1999 ), and one ( Delbroek et al, 2017 ) the instrumented TUG (iTUG, Salarian et al, 2010 ), which uses portable inertial sensors for a more detailed analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to 5T-STS is the Dynamic Gait Index (DGI), that verifies the participant’s ability to maintain the equilibrium of walking by responding to different requests. Some studies demonstrated the high reliability of the assessment in elderly people, subjects suffering from vestibular dysfunction, multiple sclerosis and post-stroke [ 15 ]. It can be performed in both hospital and home settings, as it does not require any special equipment.…”
Section: Discussionmentioning
confidence: 99%
“…It can be performed in both hospital and home settings, as it does not require any special equipment. It evaluates all aspects of gait, but takes a long time to administer (15 min) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also used the Mini-Mental Scare Examination as a screening tool for participants’ cognitive function (>24) [ 50 ]. We also used the Berg-Balance Scale (BBS) [ 51 ] and Dynamic Gait Index [ 52 ] to measure participants’ balance function. We used the Activities-specific Balance Confidence (ABC) scale [ 53 ] to evaluate participants perceived balance function during activities of daily living, and the Geriatric Depression Scale (GDS) [ 54 ] and Stroke Impact Scale (SIS) [ 55 ] to assess participant’s mental function and perceived impact of poststroke disability on their quality of life, respectively.…”
Section: Methodsmentioning
confidence: 99%